101 horror books to read before you're murdered - Hartmann, Sadie (Page Street Publishing Co., 2023)
"Curious readers and fans of monsters and the macabre, get ready to bulk up your TBR piles! Sadie "Mother Horror" Hartmann has curated the best selection of modern horror books, including plenty of deep cuts. Indulge your heart's darkest desires to be terrified, unsettled, disgusted, and heartbroken with stories that span everything from paranormal hauntings and creepy death cults to small-town terrors and apocalyptic disasters. Each recommendation includes a full synopsis as well as a quick overview of the book's themes, style, and tone so you can narrow down your next read at a glance"--